Trastorno de ansiedad por separación y su incidencia en la conducta de un niño de 9 años de edad del cantón Babahoyo - Salas Bajaña, Valeria Katiusca (2022)
In this case study, as a Mental Health professional, we decided to study separation anxiety disorder in a 9-year-old boy in the city of Babahoyo, due to the fact that he presented symptoms and signs typical of this disorder, in addition to changes in his behavior that became noticeable in the academic institution where he has been in his 4th year of basic education, where through 6 sessions with our patient, where we implemented techniques such as clinical interview, direct case observation and psychological test to identify the anxiety in childhood helped us to identify a series of eventualities that confirm our hypothesis, which ensures that the symptoms he manifests are due to the fact that he maintains separation anxiety disorder and that his parents are going through a process of separation and divorce, which It directly affects him, influencing the behavior that he maintains in different places in which he develops, likewise once the diagnosis was made, we were able to carry out a diagnostic plan that could help improve and reduce the impact that the situation of their parents had on their state of mind, showing evident improvement.